Acute kidney injury in idiopathic nephrotic syndrome of childhood is a major risk factor for the development of chronic kidney disease. (1st January 2017) - Yaseen, Afshan; Tresa, Vina; Lanewala, Ali Asghar; Hashmi, Seema; Ali, Irshad; Khatri, Sabeeta; Mubarak, Muhammed
Abstract: Background: Acute kidney injury (AKI) is an important complication of idiopathic nephrotic syndrome (INS) and is associated with adverse outcomes, especially the development of chronic kidney disease (CKD). We aimed to determine the clinical profile of children with INS who developed AKI and its short-term outcome. Material and methods: This prospective study was conducted from March 2014 to October 2015. A total of 119 children of INS (age: 2–18 years) fulfilling the pediatric RIFLE criteria for the diagnosis of AKI were enrolled and followed up for 3 months to determine the outcome. Factors predisposing to CKD were studied. Results: The mean age at presentation was 8.8 ± 3.59 years and males were 74 (62.2%). At presentation, 61 (51.3%) children were in Risk category, 43 (36.1%) in Injury category, and 15 (12.6%) in Failure category. Most of them (41.2%) had steroid-resistant nephrotic syndrome (SRNS) and focal segmental glomerulosclerosis (FSGS) on histopathology (33.6%). Infections were the major predisposing factor for AKI in 67 (56.3%) cases. Drug toxicity was the next common, found in 52 (43.7%) children. A total of 65 (54.6%) children recovered from AKI, while 54 (45.4%) did not. CKD developed in 49 (41.2%) non-recovered cases and 5 (4.2%) children succumbed to acute illness. SRNS, cyclosporine use, FSGS on histology, and drug toxicity were significant factors associated with the development of CKD. Conclusion: AKI associated with INS is a reversible condition in most cases but it can progress to CKD, especially among those who have SRNS, FSGS, and drug toxicity.